PENILAIAN KINERJA BERBASIS VALUE FOR MONEY ATAS PENERIMAAN PAJAK DAERAH KOTA PONTIANAK - Gayah, Maya Crisna (Jurnal KIAFE, 2020)
Public sector performance measurement is important to assess the accountability of the organization. Measuring performance in public sector should be done by paying attention to the concept of Value for Money that is based on three main elements, such as economy, efficiency and effectiveness. This study aims to examine performance of Badan Keuangan Daerah (BKD) of Pontianak City for years 2017 and 2018 on local tax revenue from the perspective of economy, efficiency and effectiveness. Data are analyzed using quantitative and qualitative analysis. Quantitative analysis is done by calculating economy, efficiency, and effectiveness ratios. Qualitative analysis was done by interviewing Badan Keuangan Daerah employees. The results show that the performance of Badan Keuangan Daerah of Pontianak City on local tax revenue is economical, very efficient, and effective enough.Keywords: Performance measurement, local tax, Value for Money, economic, efficiency, effectivityReferensiArdila, I., & Putri, A. N. (2015). Analisis Kinerja Keuangan Dengan Pendekatan Value for Money Pada Pengadilan Negeri Tebing Tinggi. Jurnal Riset Akuntansi dan Bisnis, 15, 78-85. doi: https://doi.org/10.30596/jrab.v15i1.428.Batian, I. (2006). Akuntansi Sektor Publik: Suatu Pengantar. Jakata: Erlangga.Dewi, N. N. T., & Sisdyani, E. A. (2013). Penilaian Kinerja atas Penerimaan Pajak Hotel dan Pajak Restoran di Dinas Pendapatan Daerah Kabupaten Karangasem. E-Jurnal Akuntansi Universitas Udayana, 2, 316-334. Retrieved from https://ojs.unud.ac.id/index.php/Akuntansi/article/view/4588Halim, A. (2002). Bunga Rampai: Manajemen Keuangan Daerah (Edisi Pertama). Yogyakarta: UPP AMP YPKN.Halim, A. (2007). Akuntansi Sektor Publik: Akuntansi Keuangan Daerah. Jakarta: Salemba Empat.Kuncoro, M. (2013). Metode Riset Untuk Bisnis & Ekonomi (Edisi 4). Jakarta: Erlangga.Mahmudi. (2010). Manajemen Kinerja Sektor Publik (Edisi kedua). Yogyakarta: UPP STIM YKPN.Mahmudi. (2013). Manajemen Kinerja Sektor Publik (Edisi Kedua). Jakarta: UPP AMP YKPN.Mahmudi. (2016). Akuntansi Sektor Publik (Edisi Revisi). Yogyakarta: UII Press.Mahsun, M. (2006). Pengukuran Kinerja Sektor Publik. Yogyakarta: BPFE.Mahsun, M. (2009). Pengukuran Kinerja Sektor Publik. Yogyakarta: BPFE.Mahsun, M., Sulistyowati, F., dan Puwanugraha, H. A. (2015). Akuntansi Sektor Publik. Yogyakarta: BPFE.Marayasa, I. M., & Jati, I. K. (2017). Penilaian Kinerja Berdasarkan Konsep Value For Money untuk Penerimaan Pajak Hotel dan Restoran. E-Jurnal Akuntansi Universitas Udayana, 20, 788-813. Retrieved from https://ojs.unud.ac.id/index.php/Akuntansi/article/view/29969Mardiasmo. (2009). Akuntansi Sektor Publik.Yogyakarta: Andi.Mulyadi. (2001). Sistem Perencanaan dan Pengendalian Manajemen. Jakarta: Salemba Empat.Nasri, L. I. S. (2018). Analisis Value for Money Anggaran Pendapatan Pada Pemerintah Kota Medan, (Skripsi yang tidak dipublikasikan), Universitas Muhammadiyah Sumatera Utara, Indonesia.Ningsih, N. H., Masyithoh, S., & Lahaya, I. A. (2017). Analisis Kinerja Kegiatan Rehabilitasi Hutan dan Lahan Berdasarkan Value for Money. Kinerja: Jurnal Ekonomi dan Manajemen Universitas Mulawarman, 14, 52-60. doi: http://dx.doi.org/10.29264/jkin.v14i1.2451.Nordiawan, D & Hertianti, A. (2010). Akuntansi Sektor Publik (Edisi 2). Jakarta: Salemba Empat.Pemerintah Kota Pontianak. (2010). Peraturan Daerah Kota Pontianak Nomor 6 Tahun 2010 tentang Pajak Daerah Kota Pontianak.Putra, A. P. A., & Wirawati, N. G. P. (2015). Penilaian Kinerja Berbasis Value for Money atas Penerimaan Pendapatan Asli Daerah Kabupaten Tabanan. E-Jurnal Akuntansi Universitas Udayana, 11, 252-268. Retrieved from https://ojs.unud.ac.id/index.php/Akuntansi/article/view/10543Putri, I. A. S. & Noviari, N. (2019). Evaluasi Kinerja Badan Pendapatan Daerah Kota Denpasar Dalam Pemungutan Pajak Bumi dan Bangunan Perdesaan Perkotaan. E-Jurnal Akuntansi Universitas Udayana, 27, 1520-1545. doi: https://doi.org/10.24843/EJA.2019.v27.i02.p26.Rai, I. G. A. (2008). Audit Kinerja Pada Sektor Publik. Jakarta: Salemba Empat.Republik Indonesia. (2004). Undang-Undang Nomor 33 Tahun 2004 tentang Perimbangan Keuangan antara Pemerintah Pusat dan Pemerintah Daerah.Republik Indonesia. (2007). Undang-Undang Nomor 28 Tahun 2007 tentang Perubahan Ketiga atas Undang-Undang Nomor 6 Tahun 1983 tentang Ketentuan Umum dan Tata Cara Perpajakan.Republik Indonesia. (2009). Undang-Undang Nomor 28 Tahun 2009 tentang Pajak Daerah dan Retribusi Daerah.Republik Indonesia. (2014). Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah.Resmi, S. (2017). Perpajakan: Teori & Kasus. Jakarta: Salemba Empat.Siahaan, M. P. (2010). Pajak Daerah & Retribusi Daerah. Jakarta: Rajawali Pers.Sugiyono. (2017). Metode Penelitian Bisnis. Bandung: Alfabeta.Ulum, I. (2012). Audit Sektor Publik. Jakarta:PT Bumi Aksara.